Salmon P. Chase papers - Chase, Salmon P. (Salmon Portland), 1808-1873.
Correspondence, memoranda, diaries, speeches, writings, financial and legal papers, biographical material, and other material pertaining to Chase's service as a U.S. senator from Ohio, as a member of Abraham Lincoln's cabinet, as U.S. secretary of the treasury, and as chief justice of the U.S. Supreme Court. Also includes material relating to his law practice in Cincinnati, Ohio, and to his activities as an abolitionist. Subjects include the Liberty Party, Ohio state and national politics, the Kansas-Nebraska Act (1854), the Civil War, national finance and the development of a national banking system, creation of a national currency, the trial and impeachment of Andrew Johnson, and Reconstruction.
Correspondents include Daniel Ammen, Flamen Ball, Dwight Bannister, James Gillespie Birney, George Carlisle, Henry Beebee Carrington, Edward I. Chase, Philander Chase, William F. Chase, Cassius Marcellus Clay, Jay Cooke, George S. Denison, Rachel Denison, Hamilton Fish, James A. Garfield, Horace Greeley, Edward Stowe Hamlin, Joshua Hanna, Rutherford Birchard Hayes, George Hoadly, Janet Ralston Chase Hoyt, John Jay, Andrew Johnson, Reverdy Johnson, A. Sankey Latty, Joshua Leavitt, Simeon Nash, George Opdyke, Richard Chappell Parsons, William S. Rosecrans, J. W. Schuckers, William Henry Seward, J. Ralston Skinner, Gerrit Smith, Hamilton Smith, Kate Chase Sprague, William Sprague, Charles Sumner, and James W. Taylor.
Microfilm edition of a portion of these papers is available
Microfilm produced from originals in the Manuscript Division.
Abolitionist, lawyer, U.S senator and governor of Ohio, U.S. secretary of the treasury, and U.S. Supreme Court chief justice.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Partial index to correspondence available in the Library of Congress Manuscript Reading Room.
Keywords: Ammen, Daniel, -- 1820-1898 -- Correspondence; Ball, Flamen -- Correspondence; Bannister, Dwight -- Correspondence; Birney, James Gillespie, -- 1792-1857 -- Correspondence; Carlisle, George -- Correspondence; Carrington, Henry Beebee, -- 1824-1912 -- Correspondence; Chase, Edward I. -- Correspondence; Chase, Philander, -- 1775-1852 -- Correspondence; Chase, William F. -- Correspondence; Clay, Cassius Marcellus, -- 1810-1903 -- Correspondence; Cooke, Jay, -- 1821-1905 -- Correspondence; Denison, George S. -- 1833-1866 -- Correspondence; Denison, Rachel -- Correspondence; Fish, Hamilton, -- 1808-1893 -- Correspondence; Garfield, James A. -- 1831-1881 -- Correspondence; Greeley, Horace, -- 1811-1872 -- Correspondence; Hamlin, Edward Stowe, -- 1808-1894 -- Correspondence; Hanna, Joshua -- Correspondence; Hayes, Rutherford Birchard, -- 1822-1893 -- Correspondence; Hoadly, George, -- 1826-1902 -- Correspondence; Hoyt, Janet Ralston Chase, -- 1847-1925 -- Correspondence; Jay, John, -- 1817-1894 -- Correspondence; Johnson, Andrew, -- 1808-1875 -- Correspondence; Johnson, Andrew, -- 1808-1875 -- Impeachment; Johnson, Reverdy, -- 1796-1876 -- Correspondence; Latty, A. Sankey -- Correspondence; Leavitt, Joshua, -- 1794-1873 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Nash, Simeon, -- 1804-1879 -- Correspondence; Opdyke, George, -- 1805-1880 -- Correspondence; Parsons, Richard Chappell, -- 1826-1899 -- Correspondence; Rosecrans, William S. -- 1819-1898 -- Correspondence; Schuckers, J. W. -- 1831-1901 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Skinner, J. Ralston -- Correspondence; Smith, Gerrit, -- 1797-1874 -- Correspondence; Smith, Hamilton -- Correspondence; Sprague, Kate Chase, -- 1840-1899 -- Correspondence; Sprague, William, -- 1830-1915 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Taylor, James W. -- 1819-1893 -- Correspondence; Chase family; United States; United States. -- Department of the Treasury. -- Office of the Secretary; United States. -- Supreme Court; Liberty Party (U.S. : 1840-1848); Antislavery movements -- United States; Banks and banking -- United States; Constitutional law -- United States; Currency question -- United States; Finance, Public -- United States; Law -- United States; National banks (United States); Practice of law -- Ohio -- Cincinnati; Reconstruction (U.S. history, 1865-1877); Slavery -- United States; Ohio -- Politics and government -- 1787-1865.; United States -- Appropriations and expenditures; United States -- Economic policy -- To 1933.; United States -- History -- Civil War, 1861-1865.